Republic of Mozambique : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper examines the macroeconomic and fiscal implications of natural gas project for Mozambique. Results, which are based on the IMF Fiscal Analysis of Resource Industries model, suggest that, by the mid-2020s, half of the country's output will be generated by natural gas. However, the fiscal revenues from the projects will remain moderate until the mid-2020s because of large depreciation costs for gas liquefaction facilities. Although the economic potential emerging from the projects is tremendous, macroeconomic and fiscal implications are quite sensitive to international commodity price developments and other risk factors, highlighting that the government's authorities would be well-advised in taking a cautious approach.